A literature review on the new polymer‐infiltrated ceramic‐network material (PICN). Issue 4 (5th February 2018) - Facenda, Júlia Cadorim; Borba, Marcia; Corazza, Pedro Henrique
Abstract: Objectives: Ceramics and composites are the most used materials for dental application. Recently, the characteristics of both were combined on the called "polymer‐infiltrated ceramic‐network" (PICN). The aim of this review is to report the behavior of PICN, comparing the findings that may support the correct clinical application. Overview: The PICN material is a structure with a sintered ceramic matrix infiltrated with a polymer matrix. Studies evaluated this material microstructure and composition, mechanical properties and adhesive behavior. The most cited mechanical properties are flexural strength, compressive strength, elastic modulus, Weibull modulus, hardness, fracture toughness and fatigue resistance. Most studies compared PICN with feldspathic porcelain, lithium disilicate glass–ceramic, lithium silicate, zirconia‐reinforced glass–ceramic, leucite reinforced glass–ceramic, polycrystalline alumina and zirconia. Other studies evaluated a similar material (a nanoceramic resin). Clinical Significance: The mechanical properties of the PICN are equivalent to the properties of nanoceramic resins, lower to lithium disilicate glass ceramic and superior to feldspathic porcelain. Yet, the findings suggest a highly resistant material to degradation at low loads (close to physiological situation) when cemented on a substrate.